Development of a Smart Internet of Things Based Motorcycle Theft Prevention System - Abdullahi, I. M.; Maliki, D.; Dauda, I. A.; Dauda, U. S.; Kigbu, G. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Motorcycle theft has become a critical security challenge globally, with existing security measures proving inadequate against sophisticated theft techniques. In Nigeria, motorcycle theft accounts for 22.2% of over 45,000 documented criminal cases by 2021, necessitating advanced technological solutions. Current motorcycle security systems lack integration, real-time monitoring capabilities, and reliable alert mechanisms, making motorcycles vulnerable to theft. This research presents an integrated Internet of Things (IoT) based motorcycle theft prevention system utilizing ESP32 microcontroller, gyroscope sensors for vibration detection, load sensors for weight monitoring, GPS for location tracking, and GSM for communication. The system incorporates a mobile application developed using Flutter for real-time monitoring and alert notifications. Experimental validation demonstrated high location tracking accuracy with minimal coordinate deviations (±0.000005 degrees), effective sensor detection capabilities across various weight ranges (5-25 kg) and vibration levels (800-3500 units), and efficient alert delivery with response times ranging from 1-14 seconds across different network providers. The developed system provides a comprehensive, cost-effective solution for motorcycle security, offering real-time monitoring, multi-channel alert mechanisms, and reliable theft detection capabilities that significantly enhance motorcycle protection compared to existing solutions.